(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2012)
A development of meiofaunal data (foraminifera) from offshore area of West Lombok was conducted on 20 marine sediment samples. The samples were taken out using a grab sampler in 1997. The purpose of this study was to apply the formula of Foraminiferal Index by Hallock et al. (2003). Another purpose of this study was to recognize its relation of white sands of Senggigi beach that was dominated by Shlumbergerella floresiana. The result of analysis showed that the value of Foraminiferal Index (FI) was varies between 1.22 and 9.81. The low value of FI (<2) was found at sites that were close to the coastal area. The values FI >2 and <4 occur at five stations that gave indication of limited environment for coral growth. Value of FI >4 that showed good water condition was found in an area surrounding small islands of Gili Trawangan, Gili Meno, Gili Air and southern part of the study area. Based on the identification of foraminiferal specimens, the occurrence of Shlumbergerella floresiana was not abundant as it was accumulated in Senggigi beach. This result showed that this species did not come from samples studied but might come from marine sediment adjacent to the Senggigi beach Keywords: Benthic foraminifera, FORAM Index, west Lombok